EXPLORATION OF MILLETS AND TRADITIONAL FOODS AS ADVOCATED IN SIDDHA MEDICINE IN PROMOTING OVERALL HEALTH, PREVENTION, AND MANAGEMENT OF DISEASES PROVIDING ESSENTIAL NUTRITION - S, Heamavathi.,M.D(s); S, Shankar.,M.D(s); S, Karthi; M, D.Saravana Devi (International Journal of Zoology, Environment and Life Sciences, 2025)
Siddha medicine, an ancient system of holistic healing, emphasizes diet as a cornerstone for health. Millets and traditional foods hold a pivotal role in balancing the body’s humors (vatham, pitham, and kapam) and providing essential nutrients. This study explores their significance in promoting health and managing diseases. Objective: To investigate the role of millets and traditional foods, as prescribed in Siddha medicine, in promoting overall health, preventing diseases, and managing chronic conditions while ensuring essential nutrition. Methods: This manuscript synthesizes data from classical Siddha texts and modern research on millets and traditional foods. The review highlights their nutritional composition, therapeutic properties, and their alignment with Siddha dietary principles. Results: Millets such as pearl millet, finger millet, foxtail millet, and barnyard millet offer diverse health benefits, including improved digestion, glycemic control, and cardiovascular health. Traditional foods like legumes, fermented dishes, and seasonal vegetables provide essential nutrients and therapeutic benefits. These foods are effective in the prevention and management of diabetes, hypertension, obesity, and digestive disorders. Conclusion: The incorporation of millets and traditional foods, as advocated in Siddha medicine, promotes a holistic approach to health and disease management. These foods offer a natural and sustainable means of achieving nutritional adequacy and preventing chronic diseases.